Single Nucleotide Polymorphisms Of Insulin-Like Growth Factor 2 (Igf-2) Gene Associated W Ith Bodyweights Of Nigerian Locally Adapted Turkey (2022)
The Insulin-Like Growth Factor 2 (IGF-2) gene was studied as a candidate gene for bodyweight of three turkey populations (Black, Spotted and White strains). The primer was designed to detect single nucleotide polymorphisms of exon2 at the IGF-2 locus by polymerase chain reaction-restriction fragment length polymorphism. Co-dominant alleles A and B corresponding to genotypes AA, AB and BB were detected at the locus tested. No significant (P>0.05) associations were recorded for all the genotypes detected with bodyweights of the population utilized at weeks 3, 7, 9, 11 and 21 but bodyweights of homozygote BB genotypes across the three strains were higher than those of AA and AB genotypes. Significant differences (P<0.05) also occurred for male and female turkeys at weeks 15 and 19. No significant (P>0.05) association of different genotypes with bodyweight at other weeks were observed (P <0.05). The products amplified displayed polymorphism and the variation in exon2 of IGF-2 gene may be a molecular marker for superior growth in the turkey populations utilized.